2010
DOI: 10.1111/j.1469-7610.2010.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prodromal eating pathology

Abstract: Prospective studies have identified factors that increase risk for eating pathology onset, including perceived pressure for thinness, thin-ideal internalization, body dissatisfaction, dietary restraint, and negative affect. Research also suggests that body dissatisfaction and dietary restraint may constitute prodromal stages of the development of eating disorders. Prevention trials indicate that interventions that reduce pressure to be thin, thin-ideal internalization, body dissatisfaction, and negative affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
126
1
13

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 65 publications
18
126
1
13
Order By: Relevance
“…Despite evidence of the effects of feelings of caloric deprivation associated with restriction in the amount of food consumed and violation of inflexible dietary rules on binge eating [13,14,23,33,50,81], 10 it has been suggested that this direction of influence may be reversed and that binge eaters may attempt to avoid and or limit the subsequent weight/body fat gain resulting from binge eating episodes via dieting [12,81,82]. The results of additional analyses (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Despite evidence of the effects of feelings of caloric deprivation associated with restriction in the amount of food consumed and violation of inflexible dietary rules on binge eating [13,14,23,33,50,81], 10 it has been suggested that this direction of influence may be reversed and that binge eaters may attempt to avoid and or limit the subsequent weight/body fat gain resulting from binge eating episodes via dieting [12,81,82]. The results of additional analyses (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Although the conflicting findings between these studies cannot be easily interpreted as Spoor et al [82] assess the latent variables via different self-report measures of restrained eating and bulimia, a possible explanation might be the difference in sample characteristics, particularly age. It might be possible that the temporal relationships between dietary restraint and binge eating are evident in 10 For contradictory findings and potential explanations especially in terms of methodological and statistical shortcomings, see [12,81]. adolescence, but not in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se ha encontrado, en estudiantes universitarios, que la comorbilidad psiquiátrica se incrementa en presencia de CAR. 19 Los síntomas depresivos son algunos de los factores de riesgo con mayor potencia para predecir TCA, según lo reportado por Jacobi et al 20 La presencia de la IIED y de IC también ha sido reportada en estudios longitudinales como factores de riesgo para TCA, 21 así como la presencia de autoestima baja antes de la aparición de este tipo de psicopatología. 22 Este trabajo tiene varios objetivos; analizar de manera separada para hombres y mujeres: 1) la relación entre CAR e IMC, 2) la interacción del IMC en la asociación de CAR con variables demográficas y psicológicas y 3) la asociación de CAR con todas las variables de estudio.…”
Section: Introductionunclassified